2017
DOI: 10.1007/s13167-017-0094-6
|View full text |Cite
|
Sign up to set email alerts
|

Postmenopausal breast cancer: European challenge and innovative concepts

Abstract: Breast cancer (BC) epidemic is recognised now worldwide as the reality of the early twenty-first century. Increasing trends in the postmenopausal BC prevalence, even for the European countries earlier demonstrating relatively stable incidence rates of the disease, are highly alarming for the healthcare givers. This new actuality requires a substantial revision of the paradigm currently applied to the BC management and creation of highly innovative concepts. Current multi-centred study highlights new complex me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 30 publications
0
18
0
Order By: Relevance
“…As mentioned, epigenetic heterogeneity in cells is significantly related to the clinical outcome of cancer patients and cancer risk individuals [178]. Multiomic cancer diagnostics, including analyses of epigenetic fluctuations, progressive screening programs, and individualized patient profiling and stratification, are demands important for clinical practice that allow and facilitate personalized predictive and preventive clinical advancements in individuals [179][180][181]. The appropriateness of specific phytochemicals/whole plant substances as an "epi-drugs" against cancer is already experimentally well-established and has considerable potential to commence a new area of individualized approaches in the medical practice management and oncological research [182].…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned, epigenetic heterogeneity in cells is significantly related to the clinical outcome of cancer patients and cancer risk individuals [178]. Multiomic cancer diagnostics, including analyses of epigenetic fluctuations, progressive screening programs, and individualized patient profiling and stratification, are demands important for clinical practice that allow and facilitate personalized predictive and preventive clinical advancements in individuals [179][180][181]. The appropriateness of specific phytochemicals/whole plant substances as an "epi-drugs" against cancer is already experimentally well-established and has considerable potential to commence a new area of individualized approaches in the medical practice management and oncological research [182].…”
Section: Discussionmentioning
confidence: 99%
“…The FS questionnaire (see Table 2) applied to the actual study has been developed at the University Ophthalmologic Hospital Basel, Switzerland [13]. The actual version of the FSquestionnaire has been recently applied to analyse the FS symptoms in related health conditions such as Bdry mouth [ 14], Sicca and Sjögren syndromes [6], as well as gynaecological diseases such as several subtypes of breast cancer and metastatic disease [15][16][17].…”
Section: -Item Questionnaire To Characterise the Flammer Syndrome (mentioning
confidence: 99%
“…There is a difference between "silent" carriers of tumor lesions and patients who are predisposed to disease development and progression; a "fertile" microenvironment that supports the tumorigenesis, tumor invasion, and metastasis can distinguish between them. The mechanisms "fertilizing" the microenvironment for the cancer advancement are not addressed in animal models but it is very well addressed by innovative PPPM strategies in cancer [1,37,38].…”
Section: Diabetes Mellitus: It Is Not All About the Insulinmentioning
confidence: 99%
“…As another example, it has been repeatedly shown that premenopausal women with breast cancer have a higher risk for brain metastasis development. Thus, the premenopausal status at the time of breast cancer diagnosis is considered as an additional risk factor for the brain metastatic lesions which were not reflected in animal models of breast cancer [32,38]. It is time to ask how could we rely on the results of animal experiments with such significant inter-and intra-species discrepancies.…”
Section: Agementioning
confidence: 99%